1988
DOI: 10.1007/bf01963092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofHaemophilus influenzae isolated from patients with otitis media

Abstract: Two hundred and twenty-three Haemophilus influenzae strains isolated from patients with otitis media throughout France were characterized by biotype, serotype, antibiotic susceptibility, type of beta-lactamase production and human erythrocyte agglutination properties. All strains fell in one of two groups. One group consisted of encapsulated type b strains, 50% of which were biotype I, often resistant to ampicillin (38.5% of beta-lactamase producing strains) and seldom positive for haemagglutination (3.8%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Teng et al (1989) reported that biotype III has a higher incidence of ampicillin resistance among the different biotypes. Dabernat et al (1988) reported that 50 % of encapsulated-type strains were biotype I, and often resistant to ampicillin (38?5 %), while 42 % of nonencapsulated strains were of biotype II with 10?6 % resistant to ampicillin. Granato et al (1983) also reported that encapsulated strains of biotype I had the highest frequency of ampicillin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Teng et al (1989) reported that biotype III has a higher incidence of ampicillin resistance among the different biotypes. Dabernat et al (1988) reported that 50 % of encapsulated-type strains were biotype I, and often resistant to ampicillin (38?5 %), while 42 % of nonencapsulated strains were of biotype II with 10?6 % resistant to ampicillin. Granato et al (1983) also reported that encapsulated strains of biotype I had the highest frequency of ampicillin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Although the majority (90%) of cases of H. influenzae-induced AOM are due to NTHi strains, Hib strains are reported to cause AOM in 10% of cases (8). We have shown that AOM can be induced experimentally in rats both by NTHi and by Hib strains (27).…”
Section: Discussionmentioning
confidence: 68%
“…The Haemophilus influenzae capsular polysaccharide, polyribosyl ribitol phosphate (PRP), plays a major role in determining the types of infections caused by this organism. Unencapsulated H. influenzae strains are responsible primarily for mucosal infections, such as otitis media, sinusitis, pneumonia, and pharyngitis (12,31,35), whereas encapsulated strains cause more invasive diseases, such as meningitis, epiglottitis, suppurative arthritis, cellulitis, and otitis media (8,28). Currently available H. influenzae type b (Hib) vaccines have been shown to be effective only against infections caused by Hib.…”
mentioning
confidence: 99%